Effect of melatonin on bone metabolism in ovariectomized rats - Ladizesky, Marta Graciela (2001)
To asses the effect of pharmacological dose of melatonin on bone metabolism in ovariectomized rats, urinary deoxypyridinoline (a marker of bone resorption) and calcium excretion, circulating levels of calcium, phosphorus and bone alkaline phosphatase  activitity (a marker of bone formation), and bone mineral density (BMD), mineral content (BMC) and bone area (BA) of total body, were measured in adult rats for up to 60 days after surgery. Rats received melatonin in the drinkling water (25ug/ml water) or drinking water alone. Urinary deoxypyridinoline increased significantly after ovariectomy by 51% (30 days after surgery) and by 47% (60 days after surgerery). The increase in urinary deoxypyridinoline found 30 days after ovariectomy was not observedin melatonin-treated rats. Urinary calcium concentration was similar in the 4 experimental groups studied, as was the circulating calcium concentration was similar in the 4 experimental groups studied, as  was the circulating calcium concentration at every time interval examined. Fifteen days after surgery, a significant increase in serum phosphorus and bone alkaline phosphatase levels occurred in ovariectomized rats receiving melatonin as compared to their controls. Sixty days after surgery BMD, BMC and BA decreased significantly in ovariectomized rats, an effect not modified by melatonin. Serum estradiol decreased significantly by 30 days after ovariectomy to attain values close to the limit of detection of the assay by 60 days after ovariectomy. The results support the conclusion that a pharmacological amount of melatonin modifies bone remodeling after ovariectomy and that the effect may need adecuate concentrations of estradiol. Keywords: Melatonin, Bone remodeling, Bone mineral content, Ovariectomy, Estradiol.